Probabilistic controllability approach to metabolic fluxes in normal and cancer tissues - Jean-Marc Schwartz (Nature Portfolio, 2019)
Metabolic rewiring is a feature of many cancers. Here, the authors combine control theory and flux correlation analysis to study the transition of healthy metabolic networks to cancer states, and find that cancer metabolism is characterized by more streamlined flux distributions.